Synthesis and characterization of supramolecular systems containing nifedipine, β-cyclodextrin and aspartic acid - Cerutti, Juan Pablo (2019)
The purpose of this work was to characterize complexes of nifedipine with β-cyclodextrin (β-CD), with and without auxiliary agents, to improve aqueous solubility and the dissolution profile of nifedipine. Complexes were characterized using infrared spectroscopy, thermoanalytical methods, powder X-Ray diffraction, scanning electron microscopy, phase solubility analysis and dissolution studies. Spatial configurations were determined by NMR and further examined using computational techniques. This investigation showed that the amino acid Asp was the most efficient auxiliary agent for multicomponent complexes. The spatial configurations were consistent with those obtained by molecular modelling; evidencing that nifedipine inserted its aromatic ring into β-CD, in all complexes, with Asp interacting with the wide hydrophilic rim of β-CD. The dissolution rates of nifedipine:β-CD:Asp complexes were significantly increased compared to those of the pure drug or nifedipine:β-CD. These results indicate that the nifedipine:β-CD:Asp system is a promising approach for the preparation of optimized formulations of nifedipine.